2006
DOI: 10.4314/ajtcam.v3i4.31176
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial activity of <i>Mammea Africana</i>

Abstract: The antimalarial activity of ethanolic stembark extract of Mammea africana was studied in vivo in mice infected with Plasmodium berghei berghei during early and established infections.Mammea africana extract(30 -90mg/kg/day) exhibited a significant (P<0.05) blood schizontocidal activity both in 4-day early infection and in established infection with a significant mean survival time comparable to that of the standard drug,chloroquine,5mg/kg/day.The stembark extract posseses a promising antiplasmodial activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…All animals belonging to groups 2-5 were immunosuppresed with an intraperitoneal stat dose of 100 mg/kg cyclophosphamide[ 11 ], followed by a booster dose of 50 mg/kg on day 8. Malaria parasite was inoculated into the rats by intraperitoneal injection of approximately 1×10 6 parasites[ 12 ] on day 12. Animals that were treated with lamivudine received 20 mg/kg daily for 21 days while those that received artesunate were treated with 10 mg/kg of artesunate starting from day 15 of the study.…”
Section: Methodsmentioning
confidence: 99%
“…All animals belonging to groups 2-5 were immunosuppresed with an intraperitoneal stat dose of 100 mg/kg cyclophosphamide[ 11 ], followed by a booster dose of 50 mg/kg on day 8. Malaria parasite was inoculated into the rats by intraperitoneal injection of approximately 1×10 6 parasites[ 12 ] on day 12. Animals that were treated with lamivudine received 20 mg/kg daily for 21 days while those that received artesunate were treated with 10 mg/kg of artesunate starting from day 15 of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Ouahouo et al (2004) reported cytotoxic coumarins with anti-microbial activity against Staphylococcus aureus from the plant stembark. The stembark has been reported to have anti-plasmodial (Okokon et al 2006), cardioprotective (Okokon and Antia,2007), anti-diabetic, hypolipidaemic , vasorelaxant (Dongmo et al 2007), antihypertensive (Nguelefack-Mbuyo et al 2008), antiinflammatory, analgesic (Okokon et al 2009), antioxidant (Nguelefack-Mbuyo et al 2010), antidiarrheal, anti-ulcer (Okokon et al 2010, immunomodulatory, anti-lesihmanial (Okokon et al 2012), depressant and anti-convulsant (Okokon and Davis, 2014) as well as nephroprotective (Okokon and Bawo, 2014) and hepatoprotective (Okokon et al 2016) activities. The stembark has been reported to have 5,-7dihydroxy-8-(12-methyl-butryl)-4-N-pentylcoumarins (Carpenter et al 1970(Carpenter et al , 1971Crichton and Waterman, 1978), 4-phenyl and 4-alkylcoumarins (Games, 1972), mesuxanthone B (Carpenter et al 1971).…”
Section: Mammeamentioning
confidence: 99%
“…Ouahouo et al, [6] reported "cytotoxic coumarins with anti-microbial activity against Staphylococcus aureus from the plant stembark". Additionally, anti-plasmodial [7], cardioprotective [8], anti-diabetic, hypolipidaemic [9,10], vasorelaxant [11] (Dongmo et al,2007), anti-hypertensive [12], anti inflammatory, analgesic [13], antioxidant [14], anti-diarrheal, anti-ulcer [15], immunomodulatory, antilesihmanial [5], depressant and anti-convulsant [16] as well as nephroprotective [17] and hepatoprotective [18],in vivo alpha amylase and alpha glucosidase inhibitory [19] activities. The stembark has been reported to have 5,-7dihydroxy-8-(12-methyl-butryl) -4 -Npentylcoumarins and mesuxanthone B [20][21][22], 4-phenyl and 4-alkylcoumarins [23].…”
Section: Introductionmentioning
confidence: 99%